Developing an Innovative Model of Curriculum and Instruction for Islamic Religious Education in Senior High Schools in Batam City - Juni Mahanis; Nunung Witono; Alpizar Alpizar; Abu Bakar (Harmony Philosophy: International Journal of Islamic Religious Studies and Sharia, 2025)
The curriculum and learning of Islamic Religious Education (PAI) at the Senior High School (SMA) level face significant challenges in line with the dynamics of modern society, especially in strategic areas such as Batam City, which is multicultural and industry-oriented. Curriculum innovation is an urgent necessity to ensure that PAI learning can meet the demands of the times and strengthen students' character. This study aims to identify and develop a relevant and applicable model of curriculum and PAI learning innovation in SMA Batam City. The research method used is qualitative with a library research approach. Data were obtained through a literature review of academic books, scientific journals, and official documents relevant to the theme of curriculum and PAI learning innovation. The analysis was conducted descriptively and analytically on various existing curriculum models and innovation processes. The results of the study show that several innovation models can be adapted in the development of PAI curriculum and learning in high schools, including the R-D-D model (Research, Development, and Diffusion), the Organizational Development model, and the Configuration model. These three models provide a systematic approach to the educational innovation process, from design and implementation to diffusion and routinization within the school environment. In addition, the proposed innovation process follows the dynamic initiation and implementation stages based on the theories of Rogers and Zaltman. In conclusion, the development of curriculum and PAI learning innovation models in SMA Batam City needs to consider the local socio-cultural conditions, teacher readiness, and institutional support. The appropriate implementation of these models is believed to improve the quality of religious education to be more contextual, adaptive, and impactful on the formation of students’ character.